Paediatric fracture dislocation of the forearm: an unusual presentation. (22nd April 2013) - Nandra, Rajpal; Subbu, Rajiv; Uppal, Harpal; Sambatakakis, Andreas
Abstract : Traumatic injuries of the elbow in children pose a diagnostic challenge. They demand precise knowledge of radiographic anatomy, growth characteristics of healthy and injured bones as well as specific fracture dynamics in this age group. Dislocation of the elbow is rare in children, accounting for 3–6% of all childhood elbow injuries. Fractures at the distal humerus and proximal forearm have been extensively discussed in the literature. We describe a unique case of a 4-year-old child presenting with a traumatic radial head fracture and ulnar dislocation not previously reported. Diagnosis and recognition of the injury pattern was fundamental in the successful management of this case. We recommend the use of CT with three-dimensional reconstructions, to fully understand the fracture pattern and dictate subsequent reduction manoeuvres during closed manipulation. Thus preventing open surgical techniques and their associated morbidities.